Effect of partial replacement of wheat flour with oyster mushroom (Pleurotus sajor-caju) powder on nutritional composition and sensory properties of butter biscuit - Wan Rosli, W.I; Nurhanan, A.R; Aishah, M.S (Universiti Kebangsaan Malaysia, 2012)
Nutrient composition and sensory investigation of butter biscuits incorporated with various levels of grey oyster mushroom (Pleurotus sajor-caju, PSC) powder were studied. The biscuits were formulated with 0, 2, 4 or 6% of PSC powder to partially replace wheat flour. Our results showed that butter biscuit formulated with 6% PSC powder significantly (p≤ 0.05) recorded the highest protein content (6.94%) as compared with control (6.50%). Meanwhile, the addition of 2% PSC powder in biscuit does not affect the fat content (20.71%) compared with control (20.52%). Both biscuits containing 4% and 6% PSC powder recorded 5.34 g/ 100 g and 5.52 g/ 100 g total dietary fibre (TDF), respectively and significantly higher (p≤0.05) than control biscuit (4.84 g/ 100 g). Biscuits formulated with 4% and 6% PSC powder had significantly higher β-glucan concentration at 0.72 and 0.79 g/ 100 g than control biscuit (0.66 g/ 100 g). In the sensory evaluation, biscuits incorporated with 2% PSC powder had the highest scores for all sensory attributes except for crispiness and flavor. Butter biscuit containing 4% PSC powder had score values of 5.5 and 4.5 for crispiness and flavor, respectively. The present study suggested that incorporation of PSC powder up to 4% to replace wheat flour improved crispiness and flavour, increased concentration of protein, dietary fibre and β-glucan but did not affect the fat content of butter biscuit.